Effect of Grain Size and Residual Strain on the Dynamic Transformation of Austenite under Plate Rolling Conditions. Issue 6 (14th April 2018) - Rodrigues, Samuel F.; Aranas, Clodualdo; Sun, Binhan; Siciliano, Fulvio; Yue, Stephen; Jonas, John J.
Abstract : When austenite is deformed within the austenite phase field, that is, above the equilibrium transformation temperature Ae3, it partially transforms dynamically into ferrite. Here, rough rolling simulations are conducted at 1100 °C on an X70 steel to study the influence of grain size and residual strain on this type of transformation. Three simulated roughing passes are applied with pass strains of 0.4 at a strain rate of 1.0 s −1 . The resulting stress–strain curves are recorded and analyzed. The volume fractions of ferrite and martensite (prior austenite) are determined on quenched samples by means of metallographic techniques. It is observed that dynamic transformation took place during the first roughing pass and that the volume fraction of transformed ferrite increases with the cumulative strain. Both the critical strain to the onset of dynamic transformation as well as the grain size decrease with pass number. Abstract : The occurrence of dynamic transformation (DT) during plate rolling at high temperature is studied. The critical strain for the onset of DT decreases when more roughing passes are applied. Strain accumulation is shown to provide the driving force for dynamic transformation. More ferrite is produced when the initial grain size is reduced.